Multiplicity, thresholds, and inactivity. Collaborative architecture studio on Ankara’s Ulus Meydani, Türkiye - Resta, Giuseppe; Gasco, Giorgio (Revista de Arquitectura, 2024)
This study explores the architectural and urban design strategies for revitalizing non-formalized open spaces within the historical context of former Ottoman cities, focusing on the Ulus central neighborhood in Ankara, Türkiye. Ulus Square served as a testing ground for a collaborative studio methodology conducted with third-year students in the Department of Architecture at Bilkent University. By examining the design studio’s efforts to integrate various architectural languages amidst Ankara’s eclectic/historicist backdrop, this paper highlights the complexities and opportunities in transforming Ulus Square into an ‘active void’. The methodology we adopted involves reimagining these open spaces through a revised understanding of spatial analysis, departing from three key principles: favoring multiplicity over uniform solutions; designing public spaces as urban thresholds; and prioritizing inactivity over complex functional programs. We observed that the charrette format, moving from collaborative visions to individual tasks, was ideal for incrementing students’ participation compared to more rigid studio structures experimented with in previous years.